Oocyte degeneration in a cohort adversely affects clinical outcomes in conventional IVF cycles: a propensity score matching study - Liu, Lanlan; Jiang, Xiaoming; Liu, Zhenfang; Chen, Jinghua; Yang, Chao; Chen, Kaijie; Yang, Xiaolian; Cai, Jiali; Ren, Jianzhi (Frontiers in Endocrinology, 2023)
Background: Oocyte degeneration was mostly described in intracytoplasmic sperm injection (ICSI) cycles, there is no report showing the relationship between oocyte degeneration and clinical outcomes in conventional in vitro fertilization (IVF) cycles. This retrospective study using propensity score matching method aimed to explore whether the presence of oocyte degeneration in conventional IVF cycles would affect the sibling embryo development potential and clinical outcomes. Methods: Patients with at least one oocyte degenerated after short-term insemination and stripping were defined as degeneration group (DEG), while patients with no oocyte degenerated were defined as non degeneration group (NON DEG). Propensity score matching method was used to control for potential confounding factors, and a multivariate logistic regression analysis was made to evaluate whether the presence of oocyte degeneration would affect cumulative live birth rate. Results: After PS matching, basic characteristics were similar between the two groups, oocyte yield was significantly higher in the DEG group than the NON DEG group (P<0.05), mature oocyte number , 2PN embryo number, 2PN embryo clearage rate, “slow” embryo number, “accelerated” embryo number, rate of cycles with total day 3 embryo extended culture, number of FET cycles, transferred embryo stage, transferred embryo number and live birth rate in fresh embryo transfer cycles were all similar between the two groups (P>0.05), but 2PN fertilization rate, available embryo number, high quality embryo number, “normal” embryo number, frozen embryo number, blastocyst formation rate and no available embryo cycle rate were all significantly lower in the DEG group than the NON DEG group (P<0.05). The cumulative live birth rate was also significantly lower in the DEG group than the NON DEG group (70.2% vs. 74.0%, P=0.0019). Multivariate logistic regression analysis further demonstrated that the presence of oocyte degeneration in conventional IVF cycles adversely affect cumulative live birth rate both before (OR=0.83, 95% CI: 0.75-0.92)) and after (OR=0.82, 95% CI: 0.72-0.93) PS matching. Conclusions: Our findings together revealed that the presence of oocyte degeneration in a cohort of oocytes may adversely affect subsequent embryo development potential and clinical outcomes in conventional IVF cycles.